DESAIN DAN VALIDASI SISTEM OTOMASI FEEDER MESIN RUN-OUT VELG STEEL UNTUK MOBIL KATEGORI I-IV MENGGUNAKAN METODE VDI 2221 - Yakub, Yunus; Erizal, Erizal; Yulianto, Adhithya Yudo (Bina Teknika, 2016)
Automation is one of method in production process in manufacturing sector. Automation changes work system of man-power become to automatically system as the result of combination beetween mechanical and electrical. Automation implemented at material transfer process in production process of steel wheel for car with category I-IV at PT. X. Material transfer of wheel has begin from welding process and going to Run-Out machine where dimension checking take place. Automatic feeder have function as a equipment to helps steel wheel transfer to Run-Out machine. With design method of VDI 2221, have result of best automatic feeder machine design concept from technical aspect and economic from some alternative concepts. At the design, feeder use pneumatic as actuator and logic of PLC program that triggered by sensor. Feeder machine produces optimalization of working time during production process because of consistency of production process. Beside of that, produces cost efficiency from investation because expenditure for man-power can be allocated to other position in production line.